Anomalous deformation mode transition in amorphous Mg-Zn-Ca thin films. (May 2018) - Fu, Y.; Cao, Q.P.; Liu, S.Y.; Wang, C.; Wang, X.D.; Zhang, D.X.; Qu, S.X.; Fecht, H.-J.; Jiang, J.Z.
Abstract: Deformation mode transition (DMT) from highly-localized to non-localized in amorphous alloy thin films (AATFs) was expected to depend on the homologous temperature. Here, DMT in Mg-Zn-Ca AATF with high homologous temperature but intrinsic brittleness was monitored during film/substrate co-bending, and its critical size for DMT is much low compared to other compositions. Intrinsically brittle nature of Mg-based AATF that facilitates the shear band to unstable crack transition may be responsible for unexpected low critical size despite of high homologous temperature. Graphical abstract: Unlabelled Image